A survey on the biological activities of selected plants used to manage diarrhoea and cancer in Vumba, Zimbabwe. - Marekerah, Lynette (2017)
Biological and antioxidant activities of Dicoma anomala, Kigelia pinnata, Pseudolachnostylis maprounelifolia and Flacourtia indica are reported. The medicinal plant extracts of different polarities were prepared and tested for antimicrobial activity using the disc diffusion method. The acetone crude extracts showed the highest activity as compared to the chloroform and petroleum ether extracts. The qualitative analysis of the extracts showed presence of tannins, saponins, phenolics, sterols, coumarins, flavonoids, reducing sugars, terpenoids, glycosides and alkaloids. Kigelia pinnata acetone crude extract had highest activity followed by chloroform and lastly petroleum ether. Flacourtia indica showed the highest antimicrobial activity in the petroleum ether extract with a zone of inhibition of 11.67 mm. The FTIR spectra showed functional groups of hydroxyls, amides, amines, ketones, aldehydes, arene rings and carboxylic derivatives. The Uv-vis showed that Kigelia pinnata and Pseudolachnostylis maprounelifolia had the highest antioxidant activity in the crude acetone extract with values of 5.9 and 5.5 μg Ascorbic Acid Equivalence AAE/10 μg/mL respectively. Flacourtia indica showed the highest antioxidant activity in the petroleum extract with a value of 3.66 μg AAE/10 μg/mL.